Siamopsis gen. nov. and five new species of the subfamily Cypridopsinae Kaufmann, 1900 (Crustacea: Ostracoda) from Thailand - Savatenalinton, Sukonthip (European Journal of Taxonomy, 2017)
Siamopsis gen. nov., described here, belongs to a group of genera with the right valve overlapping the left valve in the subfamily Cypridopsinae Kaufmann, 1900 of the family Cyprididae Baird, 1845. The distinguishing characters of the new genus are in the morphology of its valves and soft parts. The postero-dorsal margin of the internal left valve is plate-like protruded. The morphology of this plate varies in different species, e.g., some species bear a tooth-like tubercle on the plate. The posterior margin of the right valve is recurved inwardly at ca mid-height, resulting in the occurrence of a lobe-like expansion that can clearly be seen in the dorsal and caudal views of the carapace. In addition, the other diagnostic soft part features of the new genus are the cylindrical caudal ramus, the presence of two t-setae on the female A2 penultimate segment, the very elongated terminal segment of the Mx1 palp, the morphology of the two large bristles (tooth bristles) of the Mx1 third endite (one smooth, one serrated) and the absence of d-seta on T1. In the present paper, five new species are described under this new genus: Siamopsis renateae gen. et sp. nov., S. suttajiti gen. et sp. nov., S. conspecta gen. et sp. nov., S. khoratensis gen. et sp. nov. and Siamopsis planitia gen. et sp. nov. A key to the species of Siamopsis gen. nov. is also provided.